Program untuk permasalahan multiple trip vehicle routing problem (MTVRP) menggunakan algoritma memetic pada proses pendistribusian - Nuswantari, Ike Putri; Madja, Mimiep Setyowati (Universitas Negeri Malang, 2022)
In everyday life almost all problems require the help of mathematics, one of them on the transportation or on the distribution prosess. Multiple Trip Vehicle Routing Problem (MTVRP) is one of the problems related to the transportation or distribution prosess. Multiple Trip Vehicle Routing Problem (MTVRP) is defined as the problem of the Vehicle Routing Problem (VRP) with the expansion and the addition of multiple trips on the each vehicle when it distributes goods and the time window of customer service. One algorithm to solve the Multiple Trip Vehicle Routing Problem (MTVRP) is memetic algorithms. Memetic algorithm is a combination of genetic algorithm and local search procedures that intensify the search. Memetic algorithms procedures are: initialization process, evaluation process, selection, crossover process, mutation process, repair process, local search, vehicle allocation, and the best route is formed. To facilitate the search for the solution of the Multiple Trip Vehicle Routing Problem (MTVRP) especially at the time had to submit to many customers, memetic algorithms implemented in the language programming Borland Delphi. By using an program application be made, produced together with the results obtained manually route 0 – 1 – 3 – 4 – 0 – 5 – 2 – 0 with a travel time